Zonasi Agrowisata Kopi Sumedang Sebagai Upaya Konservasi Lahan Danau Sunyanyuri dan Perkebunan Kopi Rakyat - Annisa Gemilang; huda nurjanti; Firmansam Bastaman (Composite : Jurnal Ilmu Pertanian, 2021)
called Kopi Buhun. Buhun Coffee is a type of Arabica coffee which is a single origin "special tea coffee". In developing Buhun coffee, land is needed that can be planted with coffee. This land is not only a coffee plantation but can become a tourist attraction that can educate, increase recreation and protect the environment besides that it can economically increase the income of residents around agrotourism. In general, the land of Lake Sunyayuri, Cimarias Village, Pamulihan District, Sumedang Regency is an area that has the potential to become a tourist spot with an artificial lake, and a panoramic view of the hills surrounding the lake with a beautiful and calming atmosphere. The productivity of Indonesian coffee is still low compared to the potential that can be increased. The need for plantation land, especially coffee, is still lacking. Utilization of abandoned forest areas in areas with coffee potential can still be carried out, including utilizing the Pamulihan Cekdam area. What is the form of the Sumedang Coffee Agrotourism design in utilizing the existing potential into plantation tourism that provides interesting tourist experiences, recreational facilities, and social interaction as well as coffee education for visitors and the community about how to cultivate coffee from nurseries to products that can be enjoyed and provide a source of income for local communities while preserving the environment?